Communication coaching for sonographers (CCS): Preliminary evaluation of a novel intervention to improve unexpected news delivery - Judith Johnson; Essie Kaur; Jane Arezina; Louise D. Bryant; Rebecca Wallace; Gill Harrison; Ruth Bender Atik; Jen Coates; Natasha Hardicre; Roxanne Sicklen; Teresa Lardner; Karen Horwood; et al. (Elsevier, 2023)
Objective: Obstetric ultrasound scans provide real-time results. In some organisations and countries, the immediate communication of results by sonographers to patients is standard practice, but there is a lack of evidence-based training to support them with this challenging task. This pilot study evaluated a novel communication coaching intervention to improve sonographer communication. Methods: Coaches met with sonographers(N = 15) three times. Sonographers collected three audio recordings of scans involving unexpected news communication at baseline(R1), post-Session 1(R2) and post-Session 2(R3), which were rated for communication skills. Participants self-reported communication confidence and burnout before(T1) and after(T2) the intervention. Feedback was collected at T2. Data were analysed using paired-samples t-tests with bootstrapped significance estimates. Results: N = 10 sonographers completed the intervention. There were significant increases in communication skills(R1 m = 4.85, SD = 1.07; R3 m = 6.73, SD = 1.80, p = 0.003) and communication confidence(T1 m = 28.00, SD = 6.27; T2 m = 32.80, SD = 6.05, p = 0.005). There were no significant changes in burnout(p > 0.05). All respondents said they would recommend the intervention and most strongly agreed it was engaging(n = 8; 89%) and imparted useful skills(n = 8; 89%). Conclusion: Communication coaching is an acceptable, potentially effective tool for improving communication of unexpected news by sonographers in ultrasound. Innovation: This is the first evaluation of an intervention to support obstetric sonographers with news delivery.